Age and education level as indicators in acquiring ICT skills among rural entrepreneurs in Samarahan, Sarawak / Mohd Ariff Zabidi Manja …[et al.] - Hoe, Lau Sie; Engkamat, Adeline; Mathew, Vloreen Nity; Ibrahim, Zalina; Ani, Ahmad Lutfi; Zabidi Manja, Mohd Ariff (Universiti Teknologi MARA, 2021)
The ability to capitalize on the digital economy by agro-based entrepreneurs greatly depends on their ability to acquire sufficient ICT knowledge and apply ICT in the running of their businesses. While the development of digital infrastructure is aggressively planned and implemented, awareness, knowledge, and skills to support its usage may still be lacking among the rural population. This paper reports preliminary studies on the knowledge and extent of ICT usage among rural entrepreneurs in Samarahan Division of Sarawak. Data collected from questionnaires were analyzed by descriptive and inferential statistics using ANOVA. There are correlations between ICT learning ability and age, as well as education background.Although 65.2% of respondents were positive about learning ICT, the mean value, the minimum and maximum values indicated that item scores decreased as the respondent’s age was higher, suggesting that older respondents felt learning ICT is not easy. The findings also show a significant difference in the ability in learning ICT with respect to age groups (p-value = 0.015) and varying levels of education (p-value = 0.008) among the sampled population.